Prospects for social policy development of Republic of Crimea in system of coordination of social interests at regional level - E. S. Nesterenko; V. I. Skribnyj (Омский научный вестник: Серия "Общество. История. Современность")
In this article, the authors have developed a system of goals for achieving a mechanism for coordinating state social policy and social interests at the regional level. Practical results of interaction of social policy and social interests are defined. Key social problems in the Republic of Crimea are identified. Priority directions for the development of social policy in the region in the short and long term are proposed. It is concluded that for effective social development of the Peninsula, it is necessary to support priority sectors of the economy in a functioning state on the basis of stimulating economic activity of the population and creating a mechanism for social adaptation of society